Evaluation of Karst Development Based on Hydrodynamic and Hydro Geochemical Characteristics of Karstic Springs (Study area: Qalajeh Anticline and Parav Biston Block) - Shahram Bahrami; Mohamad Ali Zangane Asadi; Ali jahanfar (جغرافیا و توسعه, 2016)
Assessment of hydrodynamic and hydro geochemical characteristics of springs in karstic landforms of Zagros can be appropriate guide for determination of karst development. The aim of this study is to compare the karst development by hydrodynamic and hydro geochemical characteristics of karstic springs in Folded and High thrusted Zagros belt. In this research, recession coefficient of karstic spring hydrographs,the most important oxides existed in calcareous formations, hydrological data of springs were analyzed. First, study area landforms were identified using satellite imagery and topographic and geological maps.  After assessing the karst geomorphology and geology of the study area, the hydrograph recession coefficients of 4 springs in Folded zagros belt and 7 springs in High thrusted Zagros were calculated. Results show the close relation of litho logy/fractures with hydrological behavior of groundwater system in Zagros Folded belt  and the lack of meaningful relations between litho logy/fractures and hydrological behavior of groundwater system in High thrusted Zagros. Based on hydrodynamic and recession coefficient of springs, the enlargement degree of karst in Parav Biston block was determined 5-6. The enlargement degree of karst in Qalajeh karstic aquifer was determined 2.5 to 3. The springs flow in Parav Biston block has linear and turbulent sub regimes while Qalajeh springs have only invariable regime. Evaluation of limestone and chemical analysis of spring's waters of the  study area reveal higher purity of Biston limestone compared to Asmari limestone, hence implying that there are conduit and diffuse flow in Biston and there is diffuse flow in Qalajeh.